Both Magnetic Resonance Imaging and Computed Tomography Are Reliable and Valid in Evaluating Cystic Osteochondral Lesions of the Talus. Issue 9 (17th September 2020) - Deng, En; Gao, Lixiang; Shi, Weili; Xie, Xing; Jiang, Yanfang; Yuan, Huishu; Guo, Qinwei
Background: Compared with computed tomography (CT), magnetic resonance imaging (MRI) might overestimate the condition of osteochondral lesions of the talus (OLTs) owing to subchondral bone marrow edema and the overlying cartilage defect. However, no study has compared MRI and CT directly in evaluating OLTs with subchondral cysts. Purpose: To compare the reliability and validity of MRI and CT in evaluating OLTs with subchondral cysts. Study Design: Cohort study (diagnosis); Level of evidence, 2. Methods: An institutional radiology database was queried for inpatients diagnosed with OLTs with subchondral cysts who had undergone surgical treatment between May 2015 and October 2019. A total of 48 patients met the inclusion criteria. Based on our measurement method, 2 experienced observers who were blinded to the study independently measured the length, width, and depth of the cysts using MRI and CT. The classification of cystic lesions was also performed based on MRI and CT findings. Results: Interobserver reliability was almost perfect, with intraclass correlation coefficients (ICCs) ranging from 0.935 to 0.999. ICCs for intraobserver reliability ranged from 0.944 to 0.976. The mean size of cysts measured on MRI (length, 13.38 ± 4.23 mm; width, 9.28 ± 2.28 mm; depth, 11.54 ± 3.69 mm) was not significantly different to that evaluated on CT (length, 13.40 ± 4.08 mm; width, 9.25 ± 2.34 mm; depth, 11.32 ± 3.54 mm). The size of subchondral cysts was precisely estimated on both MRI and CT. The MRI classification and CT classification revealed almost perfect agreement (kappa = 0.831). Conclusion: With our measurement method, both MRI and CT were deemed to be reliable and valid in evaluating the size of subchondral cysts of OLTs, and the MRI classification was well-correlated with the CT classification. The presented measurement method and classification systems could provide more accurate information before surgery.